University-industry-community engagements: UiTM Johor branch chapter / Muhammad Majid ... [et al.] - Majid, Muhammad; Ramli, Mohamad Faizal; Misman, Faridah Najuna (2023)
The principal goal of business is to maximise shareholder value and to generate returns to their investors. However, Academic institutions, such as UiTM, have diverse aims. In general, UiTM has a mission of becoming a Globally Renowned University of Science, Technology, Humanities, and Entrepreneurship. Universities and industry collaborations are on the rise. Collaborations benefit institutions such as UiTM, industry partners and community immensely. This is because collaborations foster crucial synergies and initiatives that increase the potential of all parties. For businesses, partnering with institutions provides access to knowledge and research that stimulates innovation, expands their resources, and bolsters their competitive advantage. On top of that, collaborations with industry partners provide academic institutions with effective means to stay abreast of changing market and industry dynamics and to comprehend the current requirements and desires of industry players. In addition to the extensive participation of industry participants, community-university partnerships are also crucial since the business environment is always changing. UiTM Johor Branch has taken the initiative to cooperate both locally and internationally with business, government, the non-profit sector, and the community to address existing and upcoming challenges.